2021
DOI: 10.1111/tbed.14385
|View full text |Cite
|
Sign up to set email alerts
|

Red deer reveal spatial risks of Crimean‐Congo haemorrhagic fever virus infection

Abstract: Crimean‐Congo haemorrhagic fever virus (CCHFV) continues to cause new human cases in Iberia while its spatial distribution and ecological determinants remain unknown. The virus remains active in a silent tick‐animal cycle to which animals contribute maintaining the tick populations and the virus itself. Wild ungulates, in particular red deer, are essential hosts for Hyalomma ticks in Iberia, which are the principal competent vector of CCHFV. Red deer could be an excellent model to understand the ecological det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 74 publications
0
34
0
Order By: Relevance
“…Species abundance data are generally limited in space and time, especially invertebrates. Only in cases where invertebrates are of conservation interest (Micó et al, 2013), or relevant as pests (Ørsted et al, 2021), or if they are vectors of health-threatening pathogens (Jaenson et al, 2012), is there inter- We recently demonstrated the relevance of the main H. lusitanicum host in Iberia, the red deer, to map CCHFV transmission risk (Cuadrado-Matías et al, 2022). However, most infectious processes are dynamic and linked to the wide variety of environmental and population determinants that modulate the inter-and intraspecific interactions between animal species, or with pathogen vectors (Casades-Martí et al, 2020;González-Barrio, Almería, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Species abundance data are generally limited in space and time, especially invertebrates. Only in cases where invertebrates are of conservation interest (Micó et al, 2013), or relevant as pests (Ørsted et al, 2021), or if they are vectors of health-threatening pathogens (Jaenson et al, 2012), is there inter- We recently demonstrated the relevance of the main H. lusitanicum host in Iberia, the red deer, to map CCHFV transmission risk (Cuadrado-Matías et al, 2022). However, most infectious processes are dynamic and linked to the wide variety of environmental and population determinants that modulate the inter-and intraspecific interactions between animal species, or with pathogen vectors (Casades-Martí et al, 2020;González-Barrio, Almería, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This study was carried out as a representative survey of the risk for the overall human population in an area where CCHFV circulates enzootically in an animal‐tick silent cycle (Cuadrado‐Matías et al., 2022 ; Moraga‐Fernández et al., 2021 ). The 0.4% of the surface of Ciudad Real province was identified as under very high risk of CCHFV infection based on the red deer exposure risk model.…”
Section: Resultsmentioning
confidence: 99%
“…Spatial representation of the serosurvey performed in Ciudad Real province according to a gradient of increasing risk of Crimean–Congo haemorrhagic fever virus (CCHFV) infection based on a predictive model built with data from red deer ( Cervus elaphus ) surveyed across the Iberian Peninsula (Cuadrado‐Matías et al., 2022). (a) The 2020 human census ( www.ine.es/) against sample size per municipality.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations